Biocompatibility: a Criterion for Conservation - Skutch, Alexander F (Universidad de Costa Rica, 1998)
A rich ecosystem Iike a tropical rain forest contains three categories of organisms: ( 1) the sustainer green photosynthetic plants of a1l growth forms, theír poIlinators, seed dispersers, and próteétors'from injurious insects, and mostIy obscure decomposers Cif dead malter that replenish the soil's fertility; (2) the associates or "guests", a diverse group that appears to be rleither necessary foc the maintenance of the ecosystem nor injurious to it; and (3) the "enemies", predators great andsmall, parasites externa! and interna!, pathogens, etc. that torture, mutilate, oc destroy membersof the fmt two categories, which coexist harmoníously, rarely injuring on¡; another. Iurge conservationists. to give preferentia! treatment to these comp¡¡tible categories, ceasing to apply inadequate resources to theprotection oc increase of members of the third category, if nor trying to eliminate sorne of them. By promoting biocompatibility, or compatible biodiversity, instead of biodiversity of undefined limits, we might rnake a more harmonious, productive, and enjoyable natural world.